PENERAPAN MODEL VALUE CLARIFICATION TECHNIQUE (VCT) DALAM MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA PADA KELAS V SDN KRAMAT PELA 07 - Hildatul Azmaliyah; Otib Satibi Hidayat; Juhana Sakmal (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to improve student learning outcomes through the application of the Value Clarification Technique (VCT) model in Pancasila Education learning. This study used a classroom action research (CAR) design with 26 fifth-grade students of SDN Kramat Pela 07 Pagi as research subjects. Data were collected through cognitive domain learning outcome tests, observation of attitudes in the affective domain, and monitoring of teacher and student activities during the learning process. The results showed that the application of the VCT model was able to provide significant improvements in learning outcomes. In the cognitive domain, learning completeness increased from 58% in cycle I to 92% in cycle II. Improvements also occurred in the affective domain, as seen through the increase in indicators of Pancasila values. Nationalism attitudes increased from 65% to 96%, patriotism from 69% to 90%, and social attitudes from 61% to 92%. In addition, there was an increase in the quality of learning activities. Teacher activity increased from 82% in cycle I to 93% in cycle II, while student activity increased from 71% to 93%. The results of this study demonstrate that the VCT model is effective in improving student learning outcomes, both in cognitive and affective aspects. This model is able to encourage students to clarify values, understand the meaning of Pancasila values, and apply them in everyday life. Thus, the VCT model can be used as an alternative learning strategy that can improve the quality of the process and learning outcomes of Pancasila Education in elementary schools